QoS aware multicast routing protocols evaluation through simulation - Costa, António (2008)
In networking research, the simulation is often the single way to overcome the lack of equipment needed for laboratory setup of complex experimental topologies, with diverse traffic pattern scenarios. Even for simpler topologies and traffic scenarios, the simulation remains attractive due to the available facilities on data collection, graphics generation and step by step analysis of different protocol machines. Inter-domain multicast scenarios, where heterogeneous QoS requirements should be considered, is a particular example where both complexity and resources availability justify the use of simulation. This paper reports the experience gained by the usage of simulation tools in multicast routing with QoS. It is not focused on the real simulation results reported but on the process used to obtain them. NS-2 has been used as the base of this work.